Standards of CentroGraphic Analysis in an Anatolian Turkish Population - Ahmet Yagci; Sabri I. Ramoglu; Tancan Uysal; Ali I. Karaman; Erhan Ozdiler (Galenos Yayinevi, 2013)
Aim:The aims of this study were to evaluate different facial-form assessment concepts (conventional numeric cephalometric approach and geometric centroid-oriented individualized cephalomorphic approach), to establish cephalomorphic norms from lateral cephalograms of Anatolian Turkish young adults, and to identify possible gender differences between Anatolian Turkish young men and women.Materials and Methods:The subjects included 28 Turkish men (mean age, 24.33±1.66 years) and 40 Turkish women (mean age, 23.12±2.24 years) ranging from 20 to 31 years old. Conventional cephalometric analysis and CentroGraphic analysis were applied to each lateral cephalogram. To determine the errors associated with radiographic measurements, 20 radiographs were selected randomly. Their tracings and measurements were repeated 8 weeks after the first measurements. A paired sample t test was applied to the first and second measurements. An independent-samples t test was performed for statistical evaluation of gender differences.Results:Generally, some differences were observed, but most of the values for skeletal measurements in Anatolian Turkish adults for cephalometric analysis were found to be similar to the ideal norms of different authors. According to statistical analysis, cephalometric and cephalomorphic measurements were similar for men and women, except facial centroid (FC) value. The FC value for women was statistically greater than that for men (p<0.05) CentroGraphic analysis results show that Anatolian Turkish adults have protrusive mandibular and retrusive upper lip.Conclusions:It is appropriate to put these practical CentroGraphic norms into daily orthodontic practice when an Anatolian Turkish population is being treated.